Determination of endosperm protein secondary structure in hard wheat breeding lines using synchrotron infrared microspectroscopy and revelation of secondary structural changes in protein films with thermal processing - Bonwell, Emily Susanne (Kansas State University, 2008)
Fourier transform infrared microspectroscopy was used to determine protein secondary structure in hard wheat breeding lines in situ, providing a molecular means to rank endosperm hardness for the selection of wheat cultivars for a specific end-use. Mapping with a single masked spot size diameter of 4.5 [Mu]m or confocal 5 [Mu]μm on beamlines U10B and U2B, respectively, produced spectra from the subaleurone layer within each wheat kernel using the high spatial resolution available with synchrotron infrared microspectroscopy. This procedure was used for the first four crop years. A focal plane array instrument was adapted for use for the remaining two crop years with a slight reduction of spatial resolution. Deconvolution and curve fitting were applied to the amide I region of spectra selected from the interstitial protein between the starch granules, and the relative amount of [Alpha]-helix to other protein secondary structures was revealed. Over six crop years, the [Alpha]-helix to [Beta]-sheet ratio of experimental wheat varieties were compared to those of released varieties in 143 mapping experiments. The highest measurable value was 2.50 while the lowest was 1.11, a range consistent with hard wheat secondary structure determination found in previous studies (13, 16). The determination of protein secondary structure provides a means of ranking experimental breeding lines for selection in specific end-use applications. FT-IR microspectroscopic imaging was used to develop a method, using myoglobin as the model protein, to study the effects of thermal processing to 100 [degrees]C on protein secondary structure. Films cast onto highly polished stainless steel plates allowed the study of the exact same film before and after heating. Analyzing the shift in the amide I peak maxima of reflection absorption spectra for 280 pixels from myoglobin films revealed the depletion of [Alpha]-helix at the expense of other protein secondary structures. Deconvolution and curve fitting techniques were applied to the amide I region of each spectral average to model protein secondary structure components found within the region. The method developed was applied to another animal source, gelatin, and a plant source, wheat gluten.
Keywords: Protein secondary structure; Infrared; Microspectroscopy; Wheat; Agriculture, Food Science and Technology (0359)